REPRODUKSI KORUPSI : STUDI KASUS KORUPSI JAKSA URIP TRI GUNAWAN - J. Danang Widoyoko (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Judicial system in Indonesia is one of the most corrupt institution. This paper investigates how corruption becomes systemic practice and how corruption reproduced particularly in the case of bribery by Urip Tri Gunawan. Using Anthony Giddens notion on social structure as rules and resources, this paper shows how corruption has embedded in the social structure in Attorney General Office and how corruption reproduce by the repetition of social practice in the daily life of agent. As corruption has became a practical consciousness among prosecutors, it is reproduced by prosectutors wihout any consideration or conscience. Corruption has became a common practice. Corruption eradication actually is a strategy to force the agent moves from practical consciousness to discursive consciousness. Keywords : Corruption, Reproduction, Social Practices, Structure Abstrak Sistem peradilan di Indonesia adalah salah satu lembaga yang paling korup. Tulisan ini mengkaji bagaimana korupsi menjadi praktik sistemik dan bagaimana korupsi direproduksi khususnya dalam kasus suap oleh Urip Tri Gunawan. Menggunakan pengertian Anthony Giddens pada struktur sosial sebagai aturan dan sumber daya, tulisan ini menunjukkan bagaimana korupsi telah tertanam dalam struktur sosial di Kantor Kejaksaan Agung dan bagaimana korupsi berkembang biak dengan pengulangan praktek sosial dalam kehidupan sehari-hari. Korupsi telah menjadi kesadaran praktis di kalangan jaksa, hal itu direproduksi oleh jaksa tanpa pertimbangan atau hati nurani. Korupsi telah menjadi praktek umum. Pemberantasan korupsi sebenarnya merupakan strategi untuk memaksa agen bergerak dari kesadaran praktis untuk kesadaran diskursif. Kata Kunci : Korupsi, Reproduksi, Praktik Sosial, Struktur